The interference paradox (case comment) - Dickinson, AJ (Sweet and Maxwell, 2020)
Discusses the court's reasoning in SAS Institute Inc v World Programming Ltd (CA) when granting an anti-suit injunction to restrain a foreign creditor from seeking foreign court orders concerning the transfer of intangible property in the UK. Reviews the 10 steps in the court's approach, criticises its combination of national and international conflict of laws rules, and suggests why its reasoning questions traditional bases for such injunctions.